Athlete older women and sedentary controls: compairing the incidence of frailty, physical aspects and falls - Pophal da Silva, Letícia; Leal Santana, Ariadne; Sayuri Santos Suzuki, Carolina; Boneti Moreira, Natália (ABCS Health Sciences, 2020)
Introduction: The aging process results in falls, frailty, and functional dependence. However, the practice of physical exercises can prevent negative impacts on the older adult health. Objective: To compare the incidence of frailty, physical aspects, and number of falls among older adult women and sedentary controls. Methods: The study has a cross-sectional design and included 70 community-dwelling older adult women (73.96±7.52 years). The frailty phenotype (Fried Criteria) and the history of falls in the last 12 months were analyzed, followed by the evaluation of muscle power (Five times Sit-to-Stand Test), functional mobility (Time Up and Go), balance (Mini BESTest) and fear of falling (Falls Efficacy Scale). The Mann Whitney and Chi-Square tests were used for statistical analysis. Results: The frailty rate among sedentary women (Pre-frail: 42.9%; Frail: 57.1%) was different from athlete women (Non frail: 100%). The rate of falls was the same in both groups (25.7%), however, sedentary controls fell at home (100%), while older adult athlete women fell in sports activities (88.9%). The athletes showed better scores (p<0.001) in all physical aspects when compared to the sedentary controls in muscle power (11.25 vs 24.10 seconds), functional mobility (10.01 vs. 16.04 seconds), balance (27 vs 19 points) and fear of falling (16 vs 27 points). Conclusion: Ahlete older women had lower frailty rates and fear of falling, as well as better physical aspects. The characteristics of falls were different, indicating the need and the importance of contemplating the lifestyle in prevention programs promoting healthy life for older adults.